Reversible phosphorylation of proteins in proliferating and differentiating cells : cyclic variations and the effect of growth regulators / Gracinda Maria Nunes Ferreira. - Ferreira, Gracinda Maria Nunes (My University, 1994)
Living cells are highly auto-dynamic entities which means that the underlying biochemistry is equally dynamic, a reality which is ignored by most researchers. Theoretical studies indicate that such a state must be due to the existence of oscillatory variations in the levels and activities of key components in the cell. In this study, the dynamic behaviour of four major, interrelated areas of cell biochemistry (phosphorylation, dephosphorylation, the terminal reaction of glycolysis and the amount of soluble protein) were examined and all systems found to oscillate in murine erythroleukaemic cells (MEL) and, where examined, also in the human HL-60 leukaemic cell line. (Abbreviation abstract)
A Dissertation Submitted to the Faculty of SCience University of the Witwatersrand, Johannesburg In fulfilment of the requirements for the Degree of Doctor of Philosophy
Keywords: Protein kinases.; Phosphorylation.; Growth regulators